Comparison of Neoadjuvant Chemotherapy Efficiency in Advanced Ovarian Cancer Patients Treated With Paclitaxel Plus Carboplatin and Intraperitoneal Bevacizumab vs. Paclitaxel With Carboplatin - Tao, Yin; Tang, Xue-Ting; Li, Xing; Wu, An-Shan; Zhou, Hou-Shen; Zhou, Cheng-fang (Frontiers in Medicine, 2022)
Objective: This study aimed to evaluate the role of neoadjuvant chemotherapy (NACT) with bevacizumab intraperitoneal perfusion in advanced ovarian cancer. Methods: From February 2019 to October 2020, 80 patients with advanced epithelial ovarian cancer (stage IIIc or IV) were enrolled for evaluating NACT at the Central Hospital of Zhuzhou. Patients were randomized to receive paclitaxel plus carboplatin (T.C.) or T.C. plus Bevacizumab intraperitoneal perfusion (T.C.B.). The effect of Chemotherapy was assayed following two cycles of a chemotherapy regimen. CA125, tumor size, ascites, bleeding volume, duration of operation, surgical satisfaction, complication rate, and residual tumor were used to determine the therapeutic evaluation. Results: In T.C.B. groups (n=40), the level of CA125 decreased significantly(p<0.001), the ascites also reduced significantly(p<0.001); At the same time, we evaluated the intraoperative situation and found that the intraoperative blood loss in T.C.B. groups was significantly reduced(p<0.001) and shorter operation time(p<0.001). Most importantly, the satisfaction of tumor reduction has been improved in T.C.B. groups(p＜0.01). Then, we observed the postoperative recovery of the two groups, in T.C.B. groups, the postoperative wound infection, hypoproteinemia, abdominal distension, and fever were less than in T.C. groups. Finally, we analyzed the adverse reactions of the two groups during Chemotherapy, there were no severe complications in the T.C.B. groups compared with the T.C. groups, and there was no statistical significance between the two groups. Conclusions: Patients with advanced ovarian cancer get more clinical benefits from the T.C. chemotherapy regimen combined with Bevacizumab intraperitoneal perfusion than T.C. intravenous chemotherapy. Our work could improve the satisfaction of tumor reduction, provide more effective treatments to prolong the progression-free survival and reduced postoperactive complications, and promote surgical recovery in advanced ovarian cancer.